Cation-mediated optical resolution and anticancer activity of chiral polyoxometalates built from entirely achiral building blocks. Issue 7 (22nd March 2016) - Zhang, Zhi-Ming; Duan, Xiaopin; Yao, Shuang; Wang, Zhishu; Lin, Zekai; Li, Yang-Guang; Long, La-Sheng; Wang, En-Bo; Lin, Wenbin
Abstract : Homochiral polyoxometalates were optically resolved via the counter cation-mediated breaking of chiral symmetry, and showed potent cytotoxicity against various cancer cells by activating apoptotic pathways. Abstract : We report the crystallization of homochiral polyoxometalate (POM) macroanions CoSb6 O4 (H2 O)3 [Co(hmta)SbW8 O31 ]3 15− (1, hmta = hexamethylenetetramine) via the counter cation-mediated chiral symmetry breaking and asymmetric autocatalytic processes. In the presence of low Co 2+ concentrations both Δ- and Λ-enantiomers of1 formed in the reaction, crystallizing into the racemic crystal rac -1 . At a high Co 2+ concentration, the polyoxoanion enantiomers showed a high level of chiral recognition via H-bonding interactions to crystallize into enantiopure crystals of Δ- or Λ-[Co(H2 O)6 CoSb6 O4 (H2 O)3 [Co(hmta)SbW8 O31 ]3 ] 13− . During crystallization, a microscale symmetry-breaking event and a nonlinear asymmetric autocatalysis process make the enantiomers crystallize in different batches, which provides an opportunity to isolate the homochiral bulk materials. The defined structures of the racemic and homochiral crystals thus provide a molecular-level illustration that H-bonding interactions are responsible for such high-level chiral recognition, in a process similar to the supramolecular chirality frequently observed in biology. These POM macroanions showed a high cytotoxicity against various cancer cells, particularly ovarian cancer cells. The antitumor activity of these compounds resulted at least in part from the activation of the apoptotic pathways, as shown by the flow cytometry, Annexin V staining, DNA ladder, and TUNEL assay, likely by blocking the cell cycle and complexing with proteins in cells. The POM macroanions reported herein provide promising and novel antitumor agents for the potential treatment of various cancers.